Chairble / Nur Natasha Nadhira Kamal … [et al.] - Kamal, Nur Natasha Nadhira; Baharuddin, Siti Hajar Nabila; Jailani, Nur Shahirah; Jasmee, Fatin Nuraini; Turing, Nurfaqihah; Hasbullah, Nornajihah Nadia (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Nowadays, back pain has become a common disease faced by students and the elderly. This is because a slipped disc on the spine occurs as a result of incorrect posture while sitting for reciting the Quran or studying. They usually only use the study table to perform their activities without having access to back leaning support. This common practice can be observed that users always have a poor experience when using them. Therefore, we urgently need the invention of a new product that can reduce the risk of back pain for consumers. Here, we are introducing our new product invention named “Chairble” that is inspired by existing market products which are foldable sajadah with a combination of exam table products. This idea was sparked with the aim of using it as a backrest chair that can support the spine well and motivate consumers to enjoy studying or reading comfortably. This new product is created to bring a healthy lifestyle to the targeted consumers as the back pain problem can be effectively prevented. The main purpose behind this creative idea is to propose multifunctional and useful products, especially to meet the demands of targeted consumers.